Language and Reading Comprehension Abilities of Elementary School-Aged Deaf Children. (19th November 2020) - Crume, Peter K; Lederberg, Amy; Schick, Brenda
Abstract: Bilingual education programs for deaf children have long asserted that American Sign Language (ASL) is a better language of instruction English-like signing because ASL is a natural language. However, English-like signing may be a useful bridge to reading English. In the present study, we tested 32 deaf children between third and sixth grade to assess their capacity to use ASL or English-like signing in nine different languages and reading tasks. Our results found that there was no significant difference in the deaf children's ability to comprehend narratives in ASL compared to when they are told in English-like signing. Additionally, language abilities in ASL and English-like signing were strongly related to each other and to reading. Reading was also strongly related to fingerspelling. Our results suggest that there may be a role in literacy instruction for English-like signing as a supplement to ASL in deaf bilingual schools.